Pengaruh Kepemimpinan terhadap Peningkatan Kinerja dan Motivasi Pegawai Bapedda Kabupaten Penukal Abab Lematang Ilir - Mulya Hapenny; Maulana Maulana; Alamsyah Alamsyah (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
Mulya Happenny. This study aims to get an in-depth picture of the effect on improving the performance and motivation of Bappeda employees of Penukal Abab Lematang Ilir (PALI) Regency. The place that became the object of research was the Bappeda of Penukal Abab Lematang Ilir Regency which was located on Merdeka Street, Handayani Mulya Village, Talang Ubi District. The background of the problem in this study is the decline in employee performance from 2019 to 2021. Since 2020 in PALI Regency there are many echelon 2 positions. The Head of Division at Bappeda also holds the position of Head of Service in another place. So the researchers tried to examine whether there is an effect on improving the performance and motivation of employees under these conditions. The method used is a quantitative analysis method using the SPSS v 25 application. Data collection uses a Likert questionnaire. The number of samples taken was 50 employees using the saturated sample method or using the total population. Data analysis used is validity and reliability test, classical assumption test, simple linear regression analysis, and multiple linear regression as well as t-test, F test, and coefficient of determination test (Adjusted R Square). The results of the study indicate that leadership has a varied effect on increasing employee motivation and performance. Leadership in the Infrastructure Sector on improving performance with the magnitude of the influence of 25.67%, 74.5% from the Head of the Ecososbud Sector, and 26.6% from the Head of the Program. The difference in the magnitude of the effect is also shown in the employee motivation variable, namely 27.6% from the Head of the Infrastructure Division, 25.6% from the Division Head, and 30% from the Program Head. The simultaneous influence shows that leadership will affect performance improvement by 90% and 33.4% effect on employee motivation. From the results of the study, it can be suggested to the leadership to improve the quality of good leadership and make improvements in terms of coordination and communication with subordinates.